An Interactive Model of Communication between Abiotic Nanodevices and Microorganisms. (19th September 2019) - de Luis, Beatriz; Llopis‐Lorente, Antoni; Rincón, Paola; Gadea, José; Sancenón, Félix; Aznar, Elena; Villalonga, Reynaldo; Murguía, José Ramón; Martínez‐Máñez, Ramón
Abstract: The construction of communication models at the micro‐/nanoscale involving abiotic nanodevices and living organisms has the potential to open a wide range of applications in biomedical and communication technologies. However, this area remains almost unexplored. Herein, we report, as a proof of concept, a stimuli‐responsive interactive paradigm of communication between yeasts (as a model microorganism) and enzyme‐controlled Janus Au–mesoporous silica nanoparticles. In the presence of the stimulus, the information flows from the microorganism to the nanodevice, and then returns from the nanodevice to the microorganism as a feedback. Abstract : Gespräche mit Hefe : Ein interaktives Modell für die Kommunikation zwischen Hefen und enzymkontrollierten, aus Gold und mesoporösem Siliciumdioxid bestehenden Janus‐Nanopartikeln wird vorgestellt. Das Fluoreszenzsignal des Mikroorganismus (entspricht der Produktion von grünem fluoreszierendem Protein) wird durch die gezielt eindeutige Kommunikation mit dem Nanobauteil über enzymatische Reaktionen und den Austausch chemischer Botenstoffe bestimmt.